Comforts of Home: Home Care of the Terminally Ill - Fraser, Jacqueline (1990)
When a terminal illness is diagnosed, it is appropriate for the family physician to take a primary role in future management. Care goals change from being disease-focused and cure-directed to being person-focused and comfort-targeted. The patient and family comprise the unit of care. Care of the terminally ill in the home requires good planning, teamwork, excellent symptom management, and a commitment by the family physician to be available or provide alternate coverage. Death in the home should be an option for the patient and family whenever feasible. Caring for patients until death and supporting their families and friends are rewarding and positive parts of family practice.